Cultural policies and State-Nation: Statements of the Historical Heritage Property in Peru between 1821 and 2014 - Valenzuela Saldaña, Milagros (2018)
The present work analyzes the cultural policies adopted by the State for the protection and conservation of the built historic heritage and how they have evolved or not since the formation of Peru as a nation-state until the present. Additionally, it describes the criteria that have been used for the declarations of immovable property today considered historic monuments of the cultural heritage of the nation, whose conservation and sustainability is problematic due to the condition that they are in and the fact that the State regulations are too restrictive management instruments that contribute to the insustainability of such real estate in the long term.